Authorea
DOI: 10.22541/au.158446787.71423634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operation regime on bubble size and void fraction in a bubble column with porous sparger

Abstract: Performance of bubble columns under transport processes is dependent on bubble size distribution and void fraction. These multiphase parameters are sensitive to the operation regime of a bubble column. The current work presents a systematic study of bubble size and void fraction in a batch bubble column within the homogeneous and heterogeneous regimes. Effect of liquid viscosity and gas superficial velocity on bubble size distribution, void fraction, and operation regime was investigated. Results showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The viscosity of the fluid does not seem to have an influence [61], whereas Mohagheghian et al [62] reported an influence in high viscosity systems as the rising velocity of bubbles decreases, which increases the likelihood of coalescence. A higher surface tension is advantageous for coalescence, thus it destabilizes the homogenous regime [61].…”
Section: Bubble Generation From Porous Plugsmentioning
confidence: 95%
See 3 more Smart Citations
“…The viscosity of the fluid does not seem to have an influence [61], whereas Mohagheghian et al [62] reported an influence in high viscosity systems as the rising velocity of bubbles decreases, which increases the likelihood of coalescence. A higher surface tension is advantageous for coalescence, thus it destabilizes the homogenous regime [61].…”
Section: Bubble Generation From Porous Plugsmentioning
confidence: 95%
“…The transition between the homogeneous and heterogeneous regime has been studied by Kazakis et al [61] and Mohagheghian et al [62]. In addition, the influence of numerous parameters on the transition between these regimes was discussed in the review by Besagni et al [3].…”
Section: Bubble Generation From Porous Plugsmentioning
confidence: 99%
See 2 more Smart Citations